THE INFLUENCE OF DIGITAL LITERACY, LEARNING MEDIA, ONLINE LEARNING ON STUDENT LEARNING OUTCOMES OF THE FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA SEMESTER 113 - Ramadani, Novia Putri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of students' digital literacy levels, the effectiveness and quality of using learning media, as well as the effectiveness of online learning carried out during the Covid-19pandemic, either partially or simultaneously on cognitive learning outcomes in the form of semester. This research is a correlational research with a quantitative approach. The population in this study were students of the Economic Education study program, Faculty of Economics, State University of Jakarta, batch 2018-2020. With Simple Random Sampling technique with the Slovin formula the number of respondents obtained as many as 196 students. Data collection techniques using a questionnaire. The data analysis technique used is multiple regression analysis. The results showed that Digital Literacy has no significant effect on Student Learning Outcomes. There is a positive influence between Learning Media and Learning Outcomes seen from the tcount value of the learning media. There is a negative influence between Online Learning and Learning Outcomes.